Lakes and subglacial hydrological networks around Dome C, East Anatrctica - F. Rémy; L. Testut; B. Legresy; C. Bianchi; FORIERI, ALESSANDRO; I. Tabacco (International Glaciological Society, 2003)
Precise topography from European Remote-sensing Satellite radar altimetry and high density of airborne radio-echo sounding in the area surrounding Dome C, Antarctica, show a link between surface features and subglacial lakes. In this paper, we extend the study to fine structures by computing a curvature-based coefficient (c y) related to surface undulations. These coefficient variations reveal many surface undulations, and some elongated features of this parameter seem to link known subglacial lakes. A population of high values of this coefficient, assumed to correspond to transitions between sliding and non-sliding flow regime, strengthen the appearance of a network which would link most of the lakes in the area. The existence of such a network impacts on ice-flow dyna ics and on subglacial-lake studies.